2013
DOI: 10.1002/jgrd.50449
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the direct radiative effect of absorbing aerosols overlying marine boundary layer clouds in the southeast Atlantic using MODIS and CALIOP

Abstract: [1] Absorbing aerosols such as smoke strongly absorb solar radiation, particularly at ultraviolet and visible/near-infrared (VIS/NIR) wavelengths, and their presence above clouds can have considerable implications. It has been previously shown that they have a positive (i.e., warming) direct aerosol radiative effect (DARE) when overlying bright clouds. Additionally, they can cause biased passive instrument satellite retrievals in techniques that rely on VIS/NIR wavelengths for inferring the cloud optical thick… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
198
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(215 citation statements)
references
References 51 publications
15
198
2
Order By: Relevance
“…The corresponding maximum DREs for the SDD and MSD are higher by up to 3.6 W m −2 and lower by up to 1.1 W m −2 , respectively. Dust aerosols act like greenhouse gases (Miller and Tegen, 1998), trapping the outgoing terrestrial radiation while at the same time emitting radiation at longer wavelengths back to the ground and thus explaining the positive LW DREs for TOA (planetary warming) and NETSURF (surface warming). In addition, the aforementioned LW DREs (TOA and NET-SURF) covary with time, revealing that the sign and the magnitude of the LW DRE TOA are determined by the perturbation of the surface radiation budget (LW DRE NETSURF ) since the LW DRE ATM values are almost constant throughout the simulation period.…”
Section: Regional Mean Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The corresponding maximum DREs for the SDD and MSD are higher by up to 3.6 W m −2 and lower by up to 1.1 W m −2 , respectively. Dust aerosols act like greenhouse gases (Miller and Tegen, 1998), trapping the outgoing terrestrial radiation while at the same time emitting radiation at longer wavelengths back to the ground and thus explaining the positive LW DREs for TOA (planetary warming) and NETSURF (surface warming). In addition, the aforementioned LW DREs (TOA and NET-SURF) covary with time, revealing that the sign and the magnitude of the LW DRE TOA are determined by the perturbation of the surface radiation budget (LW DRE NETSURF ) since the LW DRE ATM values are almost constant throughout the simulation period.…”
Section: Regional Mean Resultsmentioning
confidence: 99%
“…As a response to these disturbances, the surface heat fluxes, both sensible (SH) and latent (LE), associated with the transfer of energy (heat) and moisture between surface and atmosphere, also change in order to balance the gain or the loss of energy at the ground level (Miller and Tegen, 1998). Subsequently, variations of SH and LE have an impact on the components of the hydrological cycle (Miller et al, 2004b) as well as on the turbulent kinetic energy and momentum transfer which in turn affect near-surface winds and dust emission (Pérez et al, 2006).…”
Section: Impact On Sensible and Latent Heat Fluxesmentioning
confidence: 99%
See 1 more Smart Citation
“…On the one hand, the evaporation of cloud droplets caused by locally absorbing aerosol makes clouds thinner, which is a radiative effect. On the other hand, the presence of absorbing aerosol may influence the satellite-retrieved COT because it can absorb radiation and thus reduce the cloud reflectance measured by the sensors on the satellite (Meyer et al, 2013(Meyer et al, , 2015Ten Hoeve et al, 2011). Meyer et al (2013) reported that adjusting for above-cloud aerosol attenuation can increase the retrieved regional mean COT by roughly 18 % for polluted marine boundary layer clouds.…”
Section: Difference Between Separated and Mixed Conditionsmentioning
confidence: 99%
“…Still, those parameters need to be used with caution. A thin layer of absorbing aerosol above clouds can trigger very high AI values especially for regions with optically thick clouds (Meyer et al, 2013;Yu et al, 2012;Alfaro-Contreras et al, 2014;Torres et al, 2012). Also, erroneously high MODIS AOD can be found over 20 cloud edges due to inaccurate cloud screening or cloud 3-D effects (Zhang et al, 2006;Shi et al, 2010).…”
Section: An Aerosol Algorithm For Heavy Smokementioning
confidence: 99%